2022
DOI: 10.1039/d2nr01568d
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona-coated immunomagnetic nanoparticles with enhanced isolation of circulating tumor cells

Abstract: Immunomagnetic nanoparticles (IMNs) have been widely developed as a detection tool to isolate rare circulating tumor cells (CTCs) from whole blood as a potential method for early cancer diagnosis, metastasis...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…As shown in Figure f, the capture performance of IMNs was 70.5%, which was lower than that in PBS (77.8%). This may be because the antibody recognition site was shielded by the protein corona formation on particles when encountered with blood proteins. , However, the capture ability of IP-CMNs (88.3%) in artificial blood samples was higher than in PBS (83.7%). These results illustrated that the IP-CMNs toward CTCs were more sensitive than IMNs.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure f, the capture performance of IMNs was 70.5%, which was lower than that in PBS (77.8%). This may be because the antibody recognition site was shielded by the protein corona formation on particles when encountered with blood proteins. , However, the capture ability of IP-CMNs (88.3%) in artificial blood samples was higher than in PBS (83.7%). These results illustrated that the IP-CMNs toward CTCs were more sensitive than IMNs.…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies have reported that a preformed protein corona, serving as a protective coating for nanoparticles, could reduce the nonspecific protein binding upon blood administration and increase the escape ability toward macrophages to prolong the circulation time. Furthermore, some reports demonstrated that protein pre-adsorption may be required as a stealth layer of nanoparticles to prevent nonspecific cellular uptake. , A high cellular internalization of nanoparticles was observed when the cells were cultured without serum proteins. In contrast, no significant cellular uptake of the stealth nanoparticles precoated with proteins was found.…”
Section: Introductionmentioning
confidence: 99%
“…Blood purification materials such as activated carbon, polysaccharides, and synthetic resins , are widely used because of their large specific surface area, excellent biocompatibility, ease of synthesis, and large exchange capacity. The development of new adsorbent materials with various continues apace, such as new carbon materials, magnetic nanoparticles, natural and synthetic polymers, composite materials, , and renewable stimuli-responsive adsorbents , has been applied to the removal of harmful substances from blood. These new materials exhibit greatly improved adsorption performance and excellent biocompatibilityan important criterion for evaluating hemoperfusion adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Therefore, isolation and enumeration of CTCs DOI: 10.1002/adfm.202304426 may play an important role in early cancer diagnosis and treatment progress monitoring. [3,4] In recent years, numerous platforms for the detection of CTCs have been developed to isolate CTCs from whole blood, such as immunomagnetic nanoparticles (IMNs), [5][6][7] antibody-conjugated microfluidic chips, [8][9][10] and size exclusion filtration. [11][12][13] Among them, IMNs have attracted extensive attention owing to their easy manipulation, high capture performance, and rapid isolation.…”
Section: Introductionmentioning
confidence: 99%